The microbiome and the gut-lung axis in tuberculosis: interplay in the course of disease and treatment - Alvarado-Peña, Néstor; Galeana-Cadena, David; Gómez-García, Itzel Alejandra; Mainero, Xavier Soberón; Silva-Herzog, Eugenia (Frontiers in Microbiology, 2023)
Tuberculosis is a chronic infectious disease caused by Mycobacterium tuberculosis (MTB) that remains a significant global health challenge. The extensive use of antibiotics in tuberculosis treatment, disrupts the delicate balance of the microbiota in various organs, including the gastrointestinal and respiratory systems. This gut-lung axis involves dynamic interactions among immune cells, microbiota, and signaling molecules from both organs. The alterations of the microbiome resulting from anti-TB treatment can significantly influence the development of tuberculosis, impacting aspects such as complete healing, reinfection, and relapse. This review aims to provide a comprehensive understanding of the gut-lung axis in the context of tuberculosis, with a specific focus on the impact of anti-TB treatment on the microbiome.